ANALISA PENGARUH VARIASI WAKTU PROSES TEMPERING TERHADAP NILAI KEKERASAN BAJA SUP 9 - Agus Setyo Umartono, M.T; Masrufaiyah S.Si, MT; Zaenal Abidin, S.T (Wahana Teknik, 2021)
The function of the spring is to accept dynamic loads and hold it for a certain time and then release it. Under these conditions the spring steel must have a good level of elasticity to be used as a spring. Cooling media during the quenching process and holding time during tempering have a very important role in determining the hardness value of the resulting material, the hardness value is influenced by changes in the microstructure that occur in the material. The research was conducted at the laboratorium PT. Indospring Tbk Gresik and data collection from November 20, 2021. After a series of tests and discussions were carried out, several conclusions were obtained from the final project research which can be described as follows In the quenching-tempering process, the mechanical properties of the JIS SUP 9 material are obtained as follows. The lowest hardness value is in the 90 minute tempering time variation with HBD value 2.85 • The highest hardness value is in the 50 minute tempering time variation. With an HBD value of 3.17 ,The hardness value that most conforms to the standard is in the variation of the tempering time of 60-90 minutes with an HBD value of 2.86-2.97 2. The JIS SUP 9 material which is subjected to a quenching – tempering heat treatment process meets the quality standards of spring feasibility